The effect of alcohol consumption on human physiological and perceptual responses to heat stress: a systematic scoping review - Nathan B. Morris; Nicholas Ravanelli; Georgia K. Chaseling (BMC, 2024)
Abstract Background Ethyl alcohol (ethanol) consumption is ostensibly known to increase the risk of morbidity and mortality during hot weather and heatwaves. However, how alcohol independently alters physiological, perceptual, and behavioral responses to heat stress remains poorly understood. Therefore, we conducted a systematic scoping review to understand how alcohol consumption affects thermoregulatory responses to the heat. Methods We searched five databases employing the following eligibility criteria, studies must have: 1) involved the oral consumption of ethanol, 2) employed a randomized or crossover-control study design with a control trial consisting of a volume-matched, non-alcoholic beverage, 3) been conducted in healthy adult humans, 4) reported thermophysiological, perceptual, hydration status markers, and/or behavioral outcomes, 5) been published in English, 6) been conducted in air or water at temperatures of > 28°C, 7) involved passive rest or exercise, and 8) been published before October 4th, 2023. Results After removing duplicates, 7256 titles were screened, 29 papers were assessed for eligibility and 8 papers were included in the final review. Across the 8 studies, there were a total of 93 participants (93 male/0 female), the average time of heat exposure was 70 min and average alcohol dose was 0.68 g·kg1. There were 23 unique outcome variables analyzed from the studies. The physiological marker most influenced by alcohol was core temperature (lowered with alcohol consumption in 3/4 studies). Additionally, skin blood flow was increased with alcohol consumption in the one study that measured it. Typical markers of dehydration, such as increased urine volume (1/3 studies), mass loss (1/3 studies) and decreased plasma volume (0/2 studies) were not consistently observed in these studies, except for in the study with the highest alcohol dose. Conclusion The effect of alcohol consumption on thermoregulatory responses is understudied, and is limited by moderate doses of alcohol consumption, short durations of heat exposure, and only conducted in young-healthy males. Contrary to current heat-health advice, the available literature suggests that alcohol consumption does not seem to impair physiological responses to heat in young healthy males.